STRENGTHENING COMMUNITY AWARENESS OF THE IMPORTANCE OF HALAL CERTIFICATION FOR CONSUMER PRODUCTS AMONG PKK WOMEN IN SIDODADI VILLAGE, KEDATON DISTRICT, BANDAR LAMPUNG CITY - Tuti Hairani; Elfa Verda Puspita; Hendri Rudiawan; Pulung Wicaksono; Hertya Andriani; Rasty Yulia; Dwi Agung Saputra; Bambang Septiawan (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Halal certification has become an essential mechanism for ensuring that products meet Islamic requirements while also maintaining standards of safety, quality, and consumer protection. Despite its growing importance, awareness and understanding of halal certification remain relatively limited among community members, particularly women who play a central role in household purchasing decisions. This community engagement initiative was designed to enhance the knowledge and awareness of members of the Family Welfare Empowerment Organization (PKK) in Sidodadi Village, Kedaton District, Bandar Lampung City, regarding the significance of halal certification in consumer products. The program engaged 30 participants and applied a participatory educational approach consisting of counseling sessions, interactive discussions, lectures, and question-and-answer activities. Knowledge acquisition was evaluated through pre-test and post-test assessments. The findings demonstrated a marked improvement in participants’ understanding, with average scores increasing from 51.3% prior to the intervention to 94.0% afterward. The program not only strengthened participants’ awareness of halal-certified products but also encouraged more informed and responsible consumption practices. These results highlight the effectiveness of community-based halal literacy initiatives in fostering greater public understanding and supporting the development of a halal-conscious society.